Oxidative stress-induced ZEB1 acetylation drives a hybrid epithelial-mesenchymal phenotype and promotes lung metastasis in triple-negative breast cancer - Min Guo; Yan-Jing Wang; Jie Shi; Li-Xia Cao; Yang Ou; Xiao Jia; Chun-Chun Qi; Zhao-Xian Li; Yu-Xin Liu; Si-Yu Zuo; Qiu-Ying Shuai; Tian-Wen Yu; et al. (Redox Biology)
While epithelial-mesenchymal plasticity (EMP) drives cancer metastasis, its regulation by redox dynamics remains poorly understood. Herein, we identified an oxidative stress-responsive CBP/SIRT1 axis that coordinated ZEB1 acetylation at K1108 to promote lung metastasis in triple-negative breast cancer (TNBC). Mechanistically, the biochemical and functional analyses revealed that the dual-acetyltransferase CBP, through stabilization and autoacetylation by oxidative stress, formed a dynamic partnership with SIRT1 to execute precision lysine modification. This post-translational rheostat triggered the functional metamorphosis of ZEB1. During this process, ZEB1 dissociation from the transcriptional corepressor CtBP, while recruiting CBP, converts ZEB1 into a transcriptional activator of epithelial genes. The resulting hybrid epithelial‒mesenchymal phenotype orchestrated dual metastatic competence-maintaining stromal interaction capacity through partial epithelial‒mesenchymal transition (EMT) while establishing NADPH-driven redox supremacy to circumvent ferroptosis. Importantly, this acetyl switch of ZEB1 revealed a metastasis-specific therapeutic vulnerability in TNBC. Our work thus highlighted ZEB1 acetylation as a redox-interpreted mechanism coupling phenotypic plasticity with stress resistance, proposing targeted disruption of this protein post-translational modification (PTM) circuit as a precision strategy against metastatic progression.